Analysis of Performance Evaluation of Economic Development of the District / City Of Pemekaran in the Nias Region - Selamat Berkat Perlindungan Zebua (ProBisnis : Jurnal Manajemen, 2021)
This study should be analyzed and evaluated the economic development. Data used in this study are Economic Growth, Gross Regional Domestic Product at Current Market Prices, Gross Regional Domestic Product at Constant Prices, Gross Regional Domestic of Product Percapita, Regency/City Local Government Original Receipt, Income Distribution, Poverty Index, and unemployment during 2011-2015. Evaluation in this study is use the indexation method, descriptive method by analyzing the ratio between time, comparison with the achievements of the district/city division, policy recommendations, and analysis of effectiveness and relevance indicators of economic development. From the analysis conducted, the index of economic performance of the district/city division has been achieved with good and has increased.